“It Feels Like Engaging With a Friend”: Using Interpersonal Communication Strategies to Encourage Science Conversations With Lay Audiences on Social Media - Martin, Curtis; MacDonald, Bertrum H. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2019)
Social media offer the potential to facilitate two-way conversations needed for effective science communication; however, research communicators often struggle to reach lay audiences on these media. In this study, the Twitter and Instagram activity of four individual scientists in North America and Europe, acting as recognized science communicators, was compared with the activity of three marine-focused non-governmental organizations (NGOs), particularly paying attention to the strategies that encourage audience engagement in two-way conversations. The results show that a combination of interpersonal communication strategies can have an important effect on the level of lay user engagement in two-way conversations over time.